The body in the fjord - Page, Katherine Hall (Page, Katherine Hall. Faith Fairchild mystery., 1997)
Smalltown caterer and minister's wife Faith Fairchild's neighbor, Pix Miller, takes center stage, heading off to Norway to investigate the sudden disappearance of a family friend. Determined to discover the truth, Pix is drawn into a suspenseful world of intrigue, stolen antiques, secret histories, and deadly echoes from Norway's past and the Nazi occupation. Surrounded by the country's breathtaking beauty, the ever-resourceful New Englander perseveres -- until at last she finds herself face-to-face with a remorseless killer...with no way out.